Umbilical Cord Length and Intra Uterine Wellbeing - Erwin Sarwono; Disse W. S.; Oudesluys Murphy; Oosting H.; De Groot C. J. (Indonesian Pediatric Society, 1991)
The length of the umbilical cord was studied in 179 Indonesian newborn determine the normal range of cord length and its influence on the occurrence of intrapartum complications such as meconium stained amniotic fluid, asphyxia and entanglement of the cord around the fetus. The authors also attempted to investigate whether unfavourable intra uterine conditions could influence cord length. Therefore a correlation between cord length, sex, gestational age, birthweight and headcircumference was sought. The mean length of the umbilical cord was 52.2 cm, with a S.D. of 10.2 cm, ranging from 31-100 cm. Male infants had significantly longer umbilical cords than females (p = 0.02). The risk of complications increased parallel with cord length.